MIND THE MULTIPLIER: RECALIBRATING THE GROWTH FACTOR IN VALUING PUBLIC COMPANIES - Валентин Бур’янов (Економіка та суспільство, 2025)
This article revisits Benjamin Graham’s intrinsic‑value rule, adapting it to the post‑crisis investment landscape. It replaces the original fixed constants with dynamic anchors linked to prevailing bond yields and market equity‑risk premia, then recalibrates the growth multiplier through contemporary cross‑section data. The resulting formula keeps Graham’s hallmark simplicity, yet reflects today’s low‑rate environment, wider dispersion of corporate growth paths and faster information cycles. Empirical tests show the updated model distinguishes over‑ and undervalued S&P 500 shares more accurately than the classic version, while remaining transparent enough for rapid screening. The study therefore offers investors a concise, data‑aware benchmark for spotting valuation errors and lays groundwork for future sector‑specific or international extensions of Graham’s approach.